Capacitor film for wireless charging and preparation method thereof

A capacitor film with modified zinc oxide nano filler improves dielectric constant, breakdown field strength, and energy storage density by using a specific preparation method, addressing integration challenges in miniaturized electronic systems.

CN118711992BActive Publication Date: 2024-12-31NINGBO GREAT SOUTHEAST WAN XIANG SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411175591.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-31
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

Current film capacitors face challenges in achieving high dielectric constant, energy storage density, and breakdown field strength due to the use of materials like biaxially oriented polypropylene and graphene, which are costly and difficult to integrate into miniaturized electronic systems.

Method used

A capacitor film composed of 85-95% polypropylene and 5-15% modified zinc oxide nano filler, prepared by modifying zinc oxide with samarium oxide, is used, enhancing compatibility and stability through a specific preparation process involving chelating agents and surfactants, followed by calcination and stretching to improve mechanical strength.

Benefits of technology

The modified zinc oxide composite significantly improves dielectric constant, breakdown field strength, and energy storage density, while ensuring uniform dispersion and stability in the polypropylene matrix, thereby enhancing the film's performance and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a capacitor film for wireless charging and a preparation method thereof, which belongs to the technical field of capacitors. The capacitor film comprises 85-95 parts of polypropylene and 5-15 parts of nanofillers by mass; the nanofiller is modified zinc oxide, and the preparation method thereof comprises mixing zinc oxide, a chelating agent, a surfactant and water, then adding a soluble samarium salt to stir the reaction, and collecting insoluble matter; and calcining the insoluble matter to obtain modified zinc oxide. The present invention adsorbs samarium ions on the surface of zinc oxide, and after calcination, a modified zinc oxide with a samarium oxide-coated structure can be formed. The modified zinc oxide can be well dispersed in a polypropylene melt system, so that the capacitor film has good stability; the modified zinc oxide can significantly improve the breakdown field strength and energy storage density of the polypropylene system. In addition, by adjusting the temperature during longitudinal stretching and the longitudinal stretching ratio, it is beneficial to improve the mechanical strength of the film and the service life of the film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitors, and in particular to a capacitor film for wireless charging and a preparation method thereof. Background Art

[0002] High energy storage dielectric film capacitors have attracted wide attention due to their advantages of being renewable, clean, safe, and lightweight. Compared with other dielectric capacitors, film capacitors have the advantages of being small, lightweight, fast charging and discharging, long cycle life, and high reliability. They play a vital role in modern smart grid frequency modulation, new energy power generation, integrated electronic systems, and other application fields.

[0003] The current commercial film capacitors are made by winding after polymer metallization, which is easy to be shaped and placed in complex systems. However, the dielectric constant and energy storage density of the film capacitor materials used (mainly biaxially oriented polypropylene film) are low, usually occupying a large volume in electronic and electrical systems, and it is difficult to meet the requirements of miniaturization and integration. The composite of polymer and inorganic nanofiller can take advantage of the respective advantages of inorganic and organic phases to comprehensively regulate the electrical properties of the composite dielectric; at the same time, the use of polymers with higher dielectric constants can achieve better results. For example, CN116003978A discloses a film capacitor material and a preparation method thereof, wherein polyethylene naphthalate, inorganic nanofiller, and coupling agent are melt blended and extruded, and then stretched to obtain a film capacitor material, wherein the inorganic nanofiller is one or more of lanthanum oxide nanofiller and hafnium oxide nanofiller; the obtained capacitor material has high temperature resistance and high energy storage density, but this material requires more rare earth metals. CN109326443A discloses a film capacitor for a new energy vehicle fast charging system, which includes a polypropylene film and a graphene coating. The film capacitor has much better current impact resistance, short-circuit charging and discharging, and voltage resistance than ordinary metallized film capacitors, and has low heat generation and long service life. However, graphene is expensive, and the instrument precision required for the graphene coating process is high.

[0004] Therefore, it is still necessary to construct a capacitor film with a simple preparation method and a wide range of material sources. Summary of the invention

[0005] In order to solve the technical problems existing in the prior art, the present invention provides a capacitor film for wireless charging, wherein the raw materials include, by weight, 85-95 parts of polypropylene and 5-15 parts of nano filler;

[0006] The nano filler is modified zinc oxide, and the preparation method thereof comprises:

[0007] Mix zinc oxide, chelating agent, surfactant and water, then add soluble samarium salt and stir to react, and collect insoluble matter;

[0008] calcining the insoluble matter to obtain modified zinc oxide;

[0009] The mass ratio of the zinc oxide, the chelating agent, the surfactant and water is 1:0.2-0.5:0.1-0.3:40-60;

[0010] The mass of soluble samarium salt is 0.8~1.5 times that of zinc oxide.

[0011] Zinc oxide has a high dielectric constant and good insulation performance and can be used as a nanofiller. However, the compatibility between the low dielectric constant organic matrix and the high dielectric constant inorganic filler is poor, and the addition of fillers inevitably causes a decrease in the breakdown field strength; at the same time, the dielectric constant of zinc oxide is not significant compared to other ceramic materials; therefore, the present invention improves its compatibility in polymer films and improves film performance by modifying zinc oxide.

[0012] Furthermore, the modified zinc oxide is a composite material of samarium oxide coated with zinc oxide.

[0013] The modified zinc oxide of the present invention is prepared by adsorbing samarium ions on the surface of zinc oxide, and after calcination, a composite material of samarium oxide (Sm2O3) coated zinc oxide is formed. The band gap of samarium oxide is 4-6 eV, and it has high resistivity, high dielectric constant, high chemical stability and high thermal stability.

[0014] Furthermore, the chelating agent is at least one of sodium ethylenediaminetetramethylenephosphonate and hexamethylenetetramine.

[0015] Furthermore, the chelating agent is sodium ethylenediaminetetramethylenephosphonate and hexamethylenetetramine in a mass ratio of 2 to 5:1.

[0016] The invention allows samarium ions to be better adsorbed on the surface of zinc oxide by adding sodium ethylenediaminetetramethylenephosphonate and hexamethylenetetramine after matching ratio, and the formed modified zinc oxide can be well dispersed in a polypropylene melt system.

[0017] Furthermore, the surfactant is polyvinyl pyrrolidone with a molecular weight of 8000-50000.

[0018] Furthermore, the preparation method of zinc oxide comprises:

[0019] Mixing a soluble zinc salt with water in a mass ratio of 1:20-30 and adjusting the pH to 12-13 to obtain a solution;

[0020] The solution is hydrothermally reacted at 160-180° C. for 5-8 hours to obtain zinc oxide.

[0021] Furthermore, the raw materials also include 0.5 to 1 parts of antistatic agent and 1 to 2 parts of anti-adhesive agent.

[0022] Furthermore, the antistatic agent is at least one of coconut amine polyoxyethylene ether, bis-β-hydroxyethyl stearylamine, and bis-β-hydroxyethyl coconut amine.

[0023] Furthermore, the anti-adhesion agent is silicon dioxide.

[0024] Furthermore, the calcination temperature is 600-1000° C., and the calcination time is 1-24 hours.

[0025] The present invention also provides a method for preparing the above-mentioned capacitor film for wireless charging, comprising:

[0026] The polypropylene is melted, and then nano fillers, antistatic agents, and anti-blocking agents are added, mixed, and extruded to obtain a sheet-like fluid;

[0027] The sheet-like fluid is cast into sheets through a chilled roller to obtain a membrane;

[0028] The film is stretched longitudinally and transversely to obtain a capacitor film for wireless charging.

[0029] Furthermore, the thickness of the film is 1-10 μm.

[0030] Furthermore, the temperature of the chilled roller is 88-99°C.

[0031] Furthermore, the longitudinal stretching temperature is 145-150°C and the longitudinal stretching ratio is 4.7-5.1 times;

[0032] The temperature during the transverse stretching is 160-170° C., and the transverse stretching ratio is 9-10 times.

[0033] An appropriate stretching ratio is beneficial to improving the mechanical strength and service life of the film. At the same time, the surface roughness of the film can be adjusted through the processing temperature to improve the compressive strength of the film.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The present invention adsorbs samarium ions on the surface of zinc oxide, and after calcination, a modified zinc oxide composite material of samarium oxide coated with zinc oxide can be formed. The modified zinc oxide can be well dispersed in a polypropylene melt system, so that the capacitor film has good stability;

[0036] 2. The modified zinc oxide added in the present invention can significantly improve the breakdown field strength and energy storage density of the polypropylene system;

[0037] 3. The present invention helps to improve the mechanical strength and service life of the film by adjusting the temperature and longitudinal stretching ratio during longitudinal stretching. DETAILED DESCRIPTION

[0038] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0039] Some of the raw materials used in the present invention include:

[0040] Polypropylene, brand 4712E1, purchased from ExxonMobil;

[0041] Ethylenediaminetetramethylenephosphonic acid sodium, model EDTMPS, was purchased from Jiangsu Rayen Environmental Protection Technology Co., Ltd.;

[0042] Coconut amine polyoxyethylene ether, model AC-1203, purchased from Green Union (Jining) Chemical Technology Co., Ltd.;

[0043] Silica, model AM-BM-09, was purchased from Guangzhou Yinuo Chemical Technology Co., Ltd.

[0044] Other raw materials not mentioned are common raw materials in the art. The above content is only to help illustrate the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase or prepare the same / similar raw materials from the market. These contents will not be repeated in the examples.

[0045] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0046] A method for preparing a capacitor film for wireless charging, the steps are as follows:

[0047] Step 1, melt 95 parts of polypropylene at 180° C., then add 10 parts of modified zinc oxide, 0.5 parts of coconut amine polyoxyethylene ether, and 1.5 parts of silicon dioxide, mix and extrude to obtain a sheet fluid;

[0048] Step 2, adjusting the gas temperature of the chill roller and the high-pressure air knife to 95° C., casting the sheet fluid obtained in step 1 to obtain a membrane;

[0049] Step 3: The film obtained in step 2 is sequentially stretched longitudinally and transversely by a longitudinal stretching machine and a transverse stretching machine to obtain a 2 μm thick wireless charging capacitor film; wherein, during longitudinal stretching, the stretching temperature is controlled to be 150°C, and the longitudinal stretching ratio is 5 times; during transverse stretching, the stretching temperature is controlled to be 170°C and the transverse stretching ratio is 9 times. The preparation method of modified zinc oxide is as follows:

[0050] S1. 3 parts of zinc nitrate hexahydrate and 80 parts of water were stirred at a speed of 300 rpm for 15 min, and then sodium hydroxide was added to adjust the pH to 12.5 to obtain a solution, and the solution was charged into a reactor for hydrothermal reaction at 180° C. for 6 h. After naturally cooling to room temperature, the solution was filtered, washed with water and anhydrous ethanol three times each, and then dried at 120° C. for 6 h to obtain zinc oxide;

[0051] S2, 1 part of zinc oxide, 0.3 part of sodium ethylenediaminetetramethylenephosphonate, 0.2 part of polyvinylpyrrolidone with an average molecular weight of 10,000 and 50 parts of water were stirred at a speed of 300 rpm for 30 minutes and mixed evenly, then 1.2 parts of samarium nitrate hexahydrate were added, the temperature was raised to 80°C and stirred at a speed of 300 rpm for 5 hours, and after filtering, the mixture was washed with water and anhydrous ethanol three times each and then dried at 120°C for 6 hours to obtain an insoluble matter;

[0052] S3, calcining the insoluble matter in a muffle furnace at 800° C. in an air atmosphere for 2 h to obtain modified zinc oxide. Example 2

[0053] A method for preparing a capacitor film for wireless charging, compared with Example 1, the difference is that the preparation method of the modified zinc oxide is:

[0054] S1. 3 parts of zinc nitrate hexahydrate and 80 parts of water were stirred at a speed of 300 rpm for 15 min, and then sodium hydroxide was added to adjust the pH to 12.5 to obtain a solution, and the solution was charged into a reactor for hydrothermal reaction at 180° C. for 6 h. After naturally cooling to room temperature, the solution was filtered, washed with water and anhydrous ethanol three times each, and then dried at 120° C. for 6 h to obtain zinc oxide;

[0055] S2, 1 part of zinc oxide, 0.3 part of hexamethylenetetramine, 0.2 part of polyvinyl pyrrolidone with an average molecular weight of 10,000 and 50 parts of water were stirred at a speed of 300 rpm for 30 minutes and mixed evenly, then 1.2 parts of samarium nitrate hexahydrate were added, the temperature was raised to 80°C and stirred at a speed of 300 rpm for 5 hours, and after filtering, the mixture was washed with water and anhydrous ethanol three times each and then dried at 120°C for 6 hours to obtain an insoluble matter;

[0056] S3, calcining the insoluble matter in a muffle furnace at 800° C. in an air atmosphere for 2 h to obtain modified zinc oxide. Example 3

[0057] A method for preparing a capacitor film for wireless charging, compared with Example 1, the difference is that the preparation method of the modified zinc oxide is:

[0058] S1. 3 parts of zinc nitrate hexahydrate and 80 parts of water were stirred at a speed of 300 rpm for 15 min, and then sodium hydroxide was added to adjust the pH to 12.5 to obtain a solution, and the solution was charged into a reactor for hydrothermal reaction at 180° C. for 6 h. After naturally cooling to room temperature, the solution was filtered, washed with water and anhydrous ethanol three times each, and then dried at 120° C. for 6 h to obtain zinc oxide;

[0059] S2, 1 part of zinc oxide, 0.2 parts of sodium ethylenediaminetetramethylenephosphonate, 0.1 parts of hexamethylenetetramine, 0.2 parts of polyvinyl pyrrolidone with an average molecular weight of 10000 and 50 parts of water were mixed at a speed of 300 rpm for 30 minutes, and then 1.2 parts of samarium nitrate hexahydrate were added, the temperature was raised to 80°C and stirred at a speed of 300 rpm for 5 hours, and after filtering, the mixture was washed with water and anhydrous ethanol three times each and then dried at 120°C for 6 hours to obtain an insoluble matter;

[0060] S3, calcining the insoluble matter in a muffle furnace at 800° C. in an air atmosphere for 2 h to obtain modified zinc oxide. Comparative Example 1

[0061] A method for preparing a capacitor film for wireless charging, compared with Example 1, the difference is that zinc oxide is used instead of modified zinc oxide,

[0062] Wherein, the preparation method of zinc oxide is:

[0063] S1, 3 parts of zinc nitrate hexahydrate and 80 parts of water were stirred at a speed of 300 rpm for 15 minutes, and then sodium hydroxide was added to adjust the pH to 12.5 to obtain a solution, and the solution was charged into a reactor for hydrothermal reaction at 180° C. for 6 hours, and the solution was naturally cooled to room temperature, filtered, washed with water and anhydrous ethanol three times each, and then dried at 120° C. for 6 hours to obtain an insoluble matter;

[0064] S2. The insoluble matter is placed in an air atmosphere muffle furnace and calcined for 2 hours at 800° C. to obtain zinc oxide. Comparative Example 2

[0065] A method for preparing a capacitor film for wireless charging is basically the same as that of Example 1, except that the method for preparing the modified zinc oxide is:

[0066] S1. 3 parts of zinc nitrate hexahydrate and 80 parts of water were stirred at a speed of 300 rpm for 15 min, and then sodium hydroxide was added to adjust the pH to 12.5 to obtain a solution, and the solution was charged into a reactor for hydrothermal reaction at 180° C. for 6 h. After naturally cooling to room temperature, the solution was filtered, washed with water and anhydrous ethanol three times each, and then dried at 120° C. for 6 h to obtain zinc oxide;

[0067] S2, 1 part of zinc oxide, 0.2 parts of polyvinyl pyrrolidone with an average molecular weight of 10,000 and 50 parts of water were stirred at a speed of 300 rpm for 30 minutes to mix evenly, then 1.2 parts of samarium nitrate hexahydrate were added, the temperature was raised to 80°C, stirred at a speed of 300 rpm for 5 hours, filtered, washed with water and anhydrous ethanol three times each, and then dried at 120°C for 6 hours to obtain an insoluble matter;

[0068] S3, calcining the insoluble matter in a muffle furnace at 800° C. in an air atmosphere for 2 h to obtain modified zinc oxide. Comparative Example 3

[0069] A method for preparing a capacitor film for wireless charging, compared with Example 1, the difference is that no modified zinc oxide is added. Comparative Example 4

[0070] Compared with Example 3, the difference is that the temperature during longitudinal stretching is 140°C. Comparative Example 5

[0071] Compared with Example 3, the difference is that the temperature during longitudinal stretching is 155°C. Comparative Example 6

[0072] Compared with Example 3, the difference is that the longitudinal stretching ratio is 4.5 times during longitudinal stretching. Comparative Example 7

[0073] Compared with Example 3, the difference is that the longitudinal stretching ratio is 5.5 times.

[0074] Test Case

[0075] The capacitor films prepared in the embodiment and the comparative example were placed in molds respectively, and gold electrodes were plated on both sides of the samples using a vacuum ion sputtering apparatus, and then the dielectric constant was tested using an LCR meter.

[0076] After gold electrodes were sputtered on both sides of the capacitor films prepared in the examples and comparative examples, they were immersed in Galden HT insulating oil for a DC breakdown strength test. The test used copper ball-plate electrodes (the ball electrode diameter was about 3 mm). The DC voltage source used in the test was a Trek 610E high-voltage amplifier with a boost rate of 500 V / s.

[0077] The electric displacement-electric field intensity (DE) hysteresis curves of the capacitor films prepared in the embodiments and comparative examples were tested by ferroelectric analysis based on an improved Sawyer-Tower circuit. The side connected to the ferroelectric instrument was the signal acquisition end, and the side connected to the high voltage source was the high voltage input end. The energy storage density of the capacitor film was obtained by the area of ​​the DE hysteresis curve.

[0078] The above test results are shown in Table 1.

[0079] Table 1 Dielectric constant, DC breakdown strength, and energy storage density results

[0080]

[0081] It can be seen from the test results in Table 1 that compared with Comparative Example 3 of only polymer films and zinc oxide without samarium modification, the dielectric constants, DC breakdown strengths and energy storage densities of other materials are all improved. This is because the insulating zinc oxide establishes an effective barrier to hinder the movement of carriers, thereby reducing the conductivity loss. The modified zinc oxide coated with samarium oxide further enhances a more stable barrier due to the presence of samarium oxide, blocks charge migration, and suppresses leakage current. The wide-bandgap samarium oxide not only enhances the inorganic / organic interface, but also introduces the zinc oxide / samarium oxide interface to strengthen the capture and scattering of carriers, thereby effectively suppressing energy loss. At the same time, the samarium oxide coating modification also enhances the interface compatibility of zinc oxide and the polypropylene matrix, effectively adjusting the local electric field distribution at the interface.

[0082] The dielectric constant and DC breakdown strength of the capacitor film prepared by adding modified zinc oxide in Examples 1 to 3 of the present invention are improved, and the energy storage density is higher. This is because in the solution environment where polyvinyl pyrrolidone is present, sodium ethylenediaminetetramethylenephosphonate or hexamethylenetetramine can effectively adsorb samarium ions on the surface of zinc oxide, making the samarium oxide coating layer more uniform; Example 3 has the best electrical properties, because sodium ethylenediaminetetramethylenephosphonate and hexamethylenetetramine have a synergistic effect, which can better anchor the samarium ions on the surface of zinc oxide, making the coating structure more stable and uniform, further improving the compatibility of the modified zinc oxide with the polymer matrix and a stronger barrier to block charge migration.

[0083] The charge and discharge efficiency of the capacitor film was also calculated using the DE hysteresis curve at an electric field strength of 300 MV / m. The low charge and discharge efficiency means that a large amount of energy must be converted into surface energy and Joule heat of the breakdown path, which cannot contribute to the improvement of the energy storage density. The results are shown in Table 2.

[0084] Table 2 Charge and discharge efficiency results

[0085]

[0086] It can be seen from the test results in Table 2 that the capacitor film of the embodiment of the present invention has better charge and discharge efficiency. This is because the more uniform and stable samarium oxide coating structure establishes an effective barrier to hinder the movement of carriers, thereby reducing conductivity losses and improving charge and discharge efficiency.

[0087] The tensile strength of Example 3 and Comparative Examples 4 to 7 was tested with reference to the standard GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets". The temperature at which the energy storage density is maintained at 80% is taken as the maximum operating temperature of the capacitor film for wireless charging. The results are shown in Table 3.

[0088] Table 3 Tensile strength and maximum operating temperature results

[0089]

[0090] It can be seen from the results in Table 3 that adjusting the temperature during longitudinal stretching and the longitudinal stretching ratio is beneficial to improving the mechanical strength and service life of the film.

[0091] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A capacitor film for wireless charging, characterized in that: In parts by mass, the raw materials include 85-95 parts of polypropylene and 5-15 parts of nanofiller; The nanofiller is modified zinc oxide, and the preparation method thereof comprises: mixing zinc oxide, a chelating agent, a surfactant and water, then adding a soluble samarium salt to stir and react, and collecting insoluble matter; calcining the insoluble matter to obtain modified zinc oxide; The mass ratio of zinc oxide, chelating agent, surfactant and water is 1:0.2-0.5:0.1-0.3:40-60; the mass of soluble samarium salt is 0.8-1.5 times of that of zinc oxide; The chelating agent is at least one of sodium ethylenediaminetetramethylenephosphonate and hexamethylenetetramine; The surfactant is polyvinyl pyrrolidone with a molecular weight of 8000-50000.

2. The capacitor film for wireless charging according to claim 1, characterized in that: The chelating agent is sodium ethylenediaminetetramethylenephosphonate and hexamethylenetetramine in a mass ratio of 2-5:

1.

3. The capacitor film for wireless charging according to claim 1, characterized in that: The preparation method of the zinc oxide comprises: Mixing a soluble zinc salt with water in a mass ratio of 1:20-30 and adjusting the pH to 12-13 to obtain a solution; The solution is hydrothermally reacted at 160-180° C. for 5-8 hours to obtain zinc oxide.

4. The capacitor film for wireless charging according to claim 1, characterized in that: It also includes 0.5 to 1 part of antistatic agent and 1 to 2 parts of anti-adhesive agent; The antistatic agent is at least one of coconut amine polyoxyethylene ether, bis-β-hydroxyethyl stearylamine, and bis-β-hydroxyethyl coconut amine; The anti-adhesive agent is silicon dioxide.

5. A method for preparing a capacitor film for wireless charging as claimed in claim 4, characterized in that: include: The polypropylene is melted, and then nano fillers, antistatic agents, and anti-blocking agents are added, mixed, and extruded to obtain a sheet-like fluid; The sheet-like fluid is cast into sheets through a chilled roller to obtain a membrane; The film is stretched longitudinally and transversely to obtain a capacitor film for wireless charging.

6. The method for preparing a capacitor film for wireless charging according to claim 5, characterized in that: The temperature of the chilled roller is 88-99°C.

7. The method for preparing a capacitor film for wireless charging according to claim 5, characterized in that: The temperature during the longitudinal stretching is 145-150° C., and the longitudinal stretching ratio is 4.7-5.1 times.

8. The method for preparing a capacitor film for wireless charging according to claim 5, characterized in that: The temperature during the transverse stretching is 160-170° C., and the transverse stretching ratio is 9-10 times.